Linguistic, Contextual, and Experiential Equivalence Issues in the Adaptation of a Performance-Based Assessment of Generic Skills in Higher Education - Ursin, Jani; Hyytinen, Heidi; Silvennoinen, Kaisa; Toom, Auli (Frontiers in Education, 2022)
This qualitative study investigated the various linguistic, contextual, and experiential equivalence issues embedded in a performance-based instrument aimed at assessing generic skills in higher education. A rigorous translation and adaptation process (American English to Finnish) was conducted on one instrument, namely Collegiate Learning Assessment (CLA+) International. The data were obtained from cognitive laboratories (n = 13), with think-alouds and follow-up interviews conducted among Finnish undergraduate students. Content logs were created, and the data were analyzed thematically. The findings revealed that linguistic and contextual equivalence issues were more prominent than experiential ones. The findings underline how important – and potentially problematic – it is for a test to measure the same construct in a different language and culture. To achieve adequate measurement equivalence, a detailed qualitative analysis of linguistic, contextual, and experiential equivalence should be conducted as part of test adaptation.